Perturbed three-step approximation process with errors for a generalized implicit nonlinear quasivariational inclusions - M. K. Ahmad; Salahuddin (International Journal of Mathematics and Mathematical Sciences, 2006)
We initiate and develop some new perturbed three-step approximation process with errors for solving generalized implicit nonlinear quasivariational inclusions. Also, the convergence and stability of the iterative sequences with errors generated by the algorithms are presented.